Development Of Learning Tools In The Cooperative Think Pair Share (TPS) Model Integrated With Huyula Values Reviewed From The Cognitive Aspect: Pengembangan Perangkat Pembelajaran Model Kooperatif Think Pair Share (TPS) Terintegrasi Nilai-Nilai Huyula Ditinjau Dari Aspek Kognitif - Rahim, Nur Ain; Odja, Abdul Haris; Uloli, Ritin; Mursalin; Umar, Masri Kudrat; Abdjul, Tirtawaty (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to describe the validity and practicality of the learning tool of the Think Pair Share (TPS) cooperative model integrated with huyula values (cooperation). This development research implemented the ADDIE model involving 25 students in grades VIII-3, SMP Negeri 1 TAPA. The results showed that (1) the learning tools developed obtained a percentage of 3.48% with valid categories. (2) the implementation (practicality) of learning obtained a percentage of 88.98% with the